2016
DOI: 10.3389/fpls.2015.01213
|View full text |Cite
|
Sign up to set email alerts
|

Four Tomato FLOWERING LOCUS T-Like Proteins Act Antagonistically to Regulate Floral Initiation

Abstract: The transition from vegetative growth to floral meristems in higher plants is regulated through the integration of internal cues and environmental signals. We were interested to examine the molecular mechanism of flowering in the day-neutral plant tomato (Solanum lycopersicum L.) and the effect of environmental conditions on tomato flowering. Analysis of the tomato genome uncovered 13 PEBP (phosphatidylethanolamine-binding protein) genes, and found six of them were FT-like genes which named as SlSP3D, SlSP6A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 57 publications
6
60
0
Order By: Relevance
“…The promotion of flowering in the cry1a/cry2 mutant is probably mediated by SP5G. This gene, belonging to the large family of FT-like genes, is expressed at very high levels in LD and at low levels in SD photoperiods (Cao et al, 2016); SP5G is an inhibitor of flowering, as indicated by the fact that Arabidopsis overexpressors show retarded flowering and that virus-mediated silencing of the SP5G gene in tomato resulted in early flowering of tomato plants under LD conditions (Cao et al, 2016). SP5G mutants obtained by gene-editing exhibit rapid flowering and enhance the compact determinate growth habit of field tomatoes (Soyk et al, 2017).…”
Section: Both Cry1a and Cry2 Show Redundancy In Regulatingmentioning
confidence: 99%
“…The promotion of flowering in the cry1a/cry2 mutant is probably mediated by SP5G. This gene, belonging to the large family of FT-like genes, is expressed at very high levels in LD and at low levels in SD photoperiods (Cao et al, 2016); SP5G is an inhibitor of flowering, as indicated by the fact that Arabidopsis overexpressors show retarded flowering and that virus-mediated silencing of the SP5G gene in tomato resulted in early flowering of tomato plants under LD conditions (Cao et al, 2016). SP5G mutants obtained by gene-editing exhibit rapid flowering and enhance the compact determinate growth habit of field tomatoes (Soyk et al, 2017).…”
Section: Both Cry1a and Cry2 Show Redundancy In Regulatingmentioning
confidence: 99%
“…The balance of activity of florigens and antiflorigens is important for overall growth, architecture, and/or flowering. This was first elucidated for FT and TFL1-like genes in the tomato model [18][19][20]. iv.…”
Section: Introductionmentioning
confidence: 99%
“…During vegetative growth, expression of the floral activator BvFT2 is repressed by BvFT1 and flowering is initiated only following the vernalization-dependent downregulation of BvFT1 expression (Pin et al, 2010). In tomato, the FT homolog SlSP5G represses flowering under LD conditions, whereas the FT homologs SlSP5G2 and SlSP5G3 repress flowering under SD conditions (Cao et al, 2016). Floral differentiation is usually repressed by members of the TERMINAL FLOWER 1 (TFL1)-like clade of the PEBP family.…”
Section: Introductionmentioning
confidence: 99%